2018
DOI: 10.1186/s40463-018-0280-0
|View full text |Cite
|
Sign up to set email alerts
|

Cavernous sinus involvement in human papillomavirus associated oropharyngeal squamous cell carcinoma: Case report of an atypical site of distant metastasis

Abstract: BackgroundHPV-associated OSCC (HPV-OSCC) has been determined to be a distinct disease entity from non-HPV associated OSCC. Patients affected by HPV-OSCC generally have a more favourable prognosis, with improved rates of locoregional control and survival compared with their non-HPV counterparts. Despite this, HPV-OSCC has a similar rate of distant metastases. Interestingly, recent evidence has emerged that demonstrates more frequent atypical metastasis patterns when compared to non-HPV associated disease. To th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 31 publications
1
5
0
Order By: Relevance
“…PET/CT was the sole modality that detected SPTs in our patient population and demonstrated 100% NPV in ruling out SPTs of the UADT. The utility of PET/CT in the HPV+ OPSCC population is further supported by reports of a tendency for this malignancy to metastasize to atypical sites outside the UADT (e.g., liver, pancreas, vertebrae, cavernous sinus) 36–38 . While we did not detect any atypical metastatic sites within our cohort, which may be a result of insufficient sampling, a review of the cases by Muller et al revealed that all metastatic lesions were detectable on PET/CT 37 .…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…PET/CT was the sole modality that detected SPTs in our patient population and demonstrated 100% NPV in ruling out SPTs of the UADT. The utility of PET/CT in the HPV+ OPSCC population is further supported by reports of a tendency for this malignancy to metastasize to atypical sites outside the UADT (e.g., liver, pancreas, vertebrae, cavernous sinus) 36–38 . While we did not detect any atypical metastatic sites within our cohort, which may be a result of insufficient sampling, a review of the cases by Muller et al revealed that all metastatic lesions were detectable on PET/CT 37 .…”
Section: Discussionsupporting
confidence: 84%
“…The utility of PET/CT in the HPV+ OPSCC population is further supported by reports of a tendency for this malignancy to metastasize to atypical sites outside the UADT (e.g., liver, pancreas, vertebrae, cavernous sinus). [36][37][38] While we did not detect any atypical metastatic sites within our cohort, which may be a result of insufficient sampling, a review of the cases by Muller et al revealed that all metastatic lesions were detectable on PET/CT. 37 Previous prospective head to head comparison of PET/CT to different combinations of X-ray, conventional CT, and magnetic resonance imaging (MRI) has shown superiority of PET/CT in detecting both SPTs and distant metastases across HNSCC subsites.…”
Section: Discussionmentioning
confidence: 60%
“…5,6 HPVpositive oropharyngeal SCC has been recognized as a distinct disease entity from its HPV-negative counterpart, and is associated with better prognosis. 7,8 While both entities carry a similar rate of distant metastasis, HPV-positive oropharyngeal SCC has shown atypical metastatic patterns and is more probable to involve unusual sites. 8,9 We present here a case of primary HPV+ tonsillar SCC in a 77year-old man, who subsequently developed a skin lesion of the neck.…”
Section: Introductionmentioning
confidence: 99%
“…7,8 While both entities carry a similar rate of distant metastasis, HPV-positive oropharyngeal SCC has shown atypical metastatic patterns and is more probable to involve unusual sites. 8,9 We present here a case of primary HPV+ tonsillar SCC in a 77year-old man, who subsequently developed a skin lesion of the neck.…”
Section: Introductionmentioning
confidence: 99%
“…metastases to the common locations. Very few cases of OSCC metastasis to the cavernous sinus have been reported in the English literature [5][6][7]. Physicians must maintain a high index of suspicion in patients with a history of malignancy who present with symptoms involving the cavernous sinus.…”
mentioning
confidence: 99%